Enzymatic Mechanism of Leishmania major Peroxidase and the Critical Role of Specific Ionic Interactions - Chreifi, Georges (Biochemistry, 2015)
Leishmania major peroxidase (LmP) is very similar to the well-known yeast cytochrome c peroxidase (CcP). Both enzymes catalyze the peroxidation of cytochrome c. Like CcP, LmP reacts with H(2)O(2) to form Compound I, which consists of a ferryl heme and a Trp radical, Fe(IV)= O;Trp(•+). Cytochrome c (Cytc) reduces the Trp radical to give Compound II, Fe(IV)= O;Trp, which is followed by an intramolecular electron transfer to give Fe(III)–OH;Trp(•+), and in the last step, Cytc reduces the Trp radical. In this study, we have used steady-state and single-turnover kinetics to improve our understanding of the overall mechanism of LmP catalysis. While the activity of CcP greatly increases with ionic strength, the k(cat) for LmP remains relatively constant at all ionic strengths tested. Therefore, unlike CcP, where dissociation of oxidized Cytc is limiting at low ionic strengths, association/dissociation reactions are not limiting at any ionic strength in LmP. We conclude that in LmP, the intramolecular electron transfer reaction, Fe(IV)= O;Trp to Fe(III)–OH;Trp(•+), is limiting at all ionic strengths. Unlike CcP, LmP depends on key intermolecular ion pairs to form the electron transfer competent complex. Mutating these sites causes the initial rate of association to decrease by 2 orders of magnitude and a substantial decrease in k(cat). The drop in k(cat) is due to a switch in the rate-limiting step of the mutants from intramolecular electron transfer to the rate of association in forming the LmP–LmCytc complex. These studies show that while LmP and CcP form very similar complexes and exhibit similar activities, they substantially differ in how their activity changes as a function of ionic strength. This difference is primarily due to the heavy reliance of LmP on highly specific intermolecular ion pairs, while CcP relies mainly on nonpolar interactions. [Image: see text]